Pilihan Rasional dan Kesejahteraan Ekonomi: Studi Keputusan Siswa SMA Katolik Sibolga untuk Melanjutkan Pendidikan Tinggi: Rational Choice and Economic Well-Being: A Study of Senior High School Students' Decisions to Pursue Higher Education at Catholic High School Sibolga - Hutagalung, Sultan Mirza; Siregar, Hairani (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2025)
This study examines how 12th-grade students at SMA Katolik Sibolga make rational decisions regarding the pursuit of higher education under varying household economic conditions. Employing a qualitative descriptive-explorative approach grounded in Rational Choice Theory, the research involves 15 students, 6 parents, and 1 school counselor selected through purposive sampling. Data were collected through semi-structured interviews and documentation, and analyzed using Miles and Huberman’s interactive model. The findings indicate that students from low-income families tend to opt for employment to achieve economic stability unless scholarships are available, while students from high-income families view higher education as a long-term investment. Social norms, family expectations, religious values, and gender roles also shape the cost-benefit calculations made by students. This study affirms that rationality is situational, shaped by subjective perceptions of well-being and the surrounding social and economic context.